2006
DOI: 10.1016/j.devcel.2006.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Regional Morphogenesis in the Hypothalamus: A BMP-Tbx2 Pathway Coordinates Fate and Proliferation through Shh Downregulation

Abstract: A central challenge in embryonic development is to understand how growth and pattern are coordinated to direct emerging new territories during morphogenesis. Here, we report on a signaling cascade that links cell proliferation and fate, promoting formation of a distinct progenitor domain within the developing chick hypothalamus. We show that the downregulation of Shh in floor plate-like cells in the forebrain governs their progression to a distinctive, proliferating hypothalamic progenitor domain. Shh downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
199
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(210 citation statements)
references
References 54 publications
9
199
0
Order By: Relevance
“…Neural Shh in hypothalamic precursor expansion and neurogenesis Shh is needed early for proliferation in the diencephalon (Ishibashi and McMahon, 2002) and in particular in the caudal regions (Manning et al, 2006), which agrees with the reduced size of the hypothalamus in our mutant already at E9.5 (Fig. 3B).…”
Section: Discussionsupporting
confidence: 86%
“…Neural Shh in hypothalamic precursor expansion and neurogenesis Shh is needed early for proliferation in the diencephalon (Ishibashi and McMahon, 2002) and in particular in the caudal regions (Manning et al, 2006), which agrees with the reduced size of the hypothalamus in our mutant already at E9.5 (Fig. 3B).…”
Section: Discussionsupporting
confidence: 86%
“…Injection of E13.5 mouse embryos with an hybridoma producing a Shh-blocking antibody (and analyzed at E18.5) alters the distribution of RGC axons at the optic chiasm with an enlargement of the overall region occupied by RGC fibers at the midline and axon extension in aberrant directions. However, as Shh activity is important to pattern the midbrain regions surrounding the ventral hypothalamus (just adjacent to the optic chiasm) during retinal axon development (Dale et al, 1997;Barresi et al, 2005;Manning et al, 2006), it is likely that blocking Shh signaling for 5 d in developing embryos can cause patterning defects. Thus, as noted by the authors (Sánchez-Camacho and Bovolenta, 2008), it is possible that the effects observed are not due to a direct guidance effect of Shh but rather to changes in expression of other guidance cues.…”
Section: The Roles Of Shh In the Guidance Of Rgc Axonsmentioning
confidence: 99%
“…Wnt signaling also governs regionalization of the nascent hypothalamus, directing the emergence of posterior (mamillary) hypothalamus throughout development, Shh and multiple different bone morphogenetic proteins (BMPs) show dynamic spatio-temporal profiles. Expression of Shh and Shh signaling components is negatively regulated by BMP signaling (Manning et al, 2006;Ohyama et al, 2008). Studies in the limb bud show that cross talk between the BMP and Shh pathways is critical for integrated growth, pattern, and differentiation (Bénazet et al, 2009), and raises the possibility that a similar cross talk between BMP and Shh signaling regulates proliferation and spatial patterning of hypothalamic neural progenitors in a concerted manner.…”
Section: Patterning Of Developing Thalamus and Hypothalamus By Secretmentioning
confidence: 99%